2005
DOI: 10.1111/j.1067-1927.2005.130303.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic neuropathic foot ulcers and amputation

Abstract: A neuropathic foot ulcer is a severe complication of diabetes that can result in a more severe complication, a lower extremity amputation. We conducted a cohort study of 24,616 individuals with a diabetic neuropathic foot ulcer treated within a multicenter wound care network. A total of 1653 (6.7%) individuals had an amputation and 46.3% of these amputations were of a toe or ray (minor amputation). In the more than 10-year follow-up period that we studied, the percentage of those who had an amputation varied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 21 publications
5
68
1
1
Order By: Relevance
“…The presence of a foot ulcer increased the risk of LEA nearly six-fold in our patients. Several other studies have reported an independent association between foot ulceration and subsequent LEA [27,31] and the risk of LEA increases with the severity of ulceration [32]. Evidence of PAD (ABI e 0.9) was also an independent predictor of LEA, consistent with the findings of others [27,33].…”
Section: Discussionsupporting
confidence: 86%
“…The presence of a foot ulcer increased the risk of LEA nearly six-fold in our patients. Several other studies have reported an independent association between foot ulceration and subsequent LEA [27,31] and the risk of LEA increases with the severity of ulceration [32]. Evidence of PAD (ABI e 0.9) was also an independent predictor of LEA, consistent with the findings of others [27,33].…”
Section: Discussionsupporting
confidence: 86%
“…Quando se relacionou amputações e presença, diminuição e ausência dos pulsos pedioso e tibial posterior, ficou confirmado que quando há alteração desses eventos, o paciente pode evoluir para amputação caso não seja submetido a revascularização. Sendo assim, a doença arterial pode ser considerada como um dos principais fatores de risco para ulceração e, consequentemente, para amputação 19 . A palpação dos pulsos arteriais distais é considerada um instrumento de grande valia na triagem para doença oclusiva arterial 5 4,5,8,20,21 .…”
Section: Discussionunclassified
“…Recurrence rates among those with successfully treated foot ulcers may be as high as 60% [4]. Foot ulcers are the most important risk factor for lower-extremity amputations [5,6] and are associated with substantial treatment costs [7]. Moreover, foot ulceration impacts negatively on quality of life [8] and, perhaps most strikingly, diabetes patients with a history of foot ulceration have a twofold increased risk for mortality as compared with those without foot ulcers [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%